Reichsparteitag Nürnberg Ansichtskarte 1937 NSDAP Propaganda Richard... - Richard Borrmeister (Wikimedia Commons, 1937)
Carte postale ancienne issue de Wikimedia Commons. Titre: Reichsparteitag Nürnberg Ansichtskarte 1937 NSDAP Propaganda Richard BORRMEISTER Verlag Photo Hoffmann München Hitler-Junge Deutsches Jungvolk Aquarell Nazi Rally Nuremberg Postcard No known copyright restrictions 866816-000000. " Nuremberg Party Rally " (Reichsparteitag Nürnberg). Postcard showing a Hitler Youth member of the Deutsches Jungvolk, Swastikas, Nuremberg castle, etc. | signed R. Borrmeister | published by Verlag Photo Hoffmann, Munich | NSDAP propaganda
Droits : Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Château; Carte postale